Crème & Brew Café / Nur Farzanah Norarmi … [et al.] - Norarmi, Nur Farzanah; Wan Mohd Luzi, Wan Nur Syahiidah; Tajudin, Noor Husna; Aziz, Siti Fahada Noor; Muhd Sahrin, Irdina Natasya; Md. Amin, Nur Aiffa (2021)
The business plan is a guideline through day organization management. To promote the movement of this business, business planning is very important before starting a business. This business arrangement will also act as a reference for investors, as this business is most likely to have a massive opportunity and will grow as one of the industry's successful businesses. Crème and brew café are a sole proprietorship. Our focus is to serve people a perfect combination of cakes and coffee at a reasonable price. There are four manager which are Noor Husna Binti Tajudin marketing manager, Wan Nur Syahiidah Binti Wan Mohd Luzi financial manager, Nur Aiffa Binti Md Amin operational manager, and Irdina Natasya Binti Muhd Sahrin administrative manager that assisted to ensure the smooth and regulated operation of company management. We get our coffee beans from one and only coffee beans producer in Malaysia, My Liberica. It is from Kulai, Johor Bahru. It has the best quality coffee beans with the production worldwide. Liberica beans provide unique taste and flavour that are sweet and fruity, nutty and have a clean aftertaste. The objectives of crème and brew is to keep ingredients, production and facilities at a high level. Therefore, create a relationship with the buyers. The passion in baking and the taste satisfied customers and we will be working hard to meet customer expectations. We have chosen to begin our business at Georgetown, Pulau Pinang where that location is popular among tourists. The community atmosphere and also close to the city with different facilities, the business location is also ideal for all customers who can easily access our location. We have set an aim to open another branch of the company and to be a well-known café in Malaysia. I believe that good planning helps us to find more funds in this financial component. To expand this company to the next stage of industry, which is a period of growth after our own brand satisfies the demand in Malaysia.